The role of the stratosphere in subseasonal to seasonal prediction: 2. Predictability arising from stratosphere ‐ troposphere coupling - Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Butler, Amy H.; Charlton-Perez, Andrew; Ayarzagüena, Blanca; Baldwin, Mark P.; Dunn-Sigouin, Etienne; Furtado, Jason C.; Garfinkel, Chaim I.; Hitchcock, Peter; Karpechko, Alexey Yu.; Kim, Hera; et al. (Journal of Geophysical Research: Atmospheres, 2020)
ISSN:0148-0227 ISSN:2169-897X